Method for compensation of transverse dispersion in electro-holography - Yu, Yingjie (2017)
In the process of optoelectronic reconstruction of color holograms, the reconstructed images of three colors can't be overlap properly because transverse dispersion caused by different wavelengths of three laser beams of R, G, B colors. In this paper, a novel method is proposed to compress or expand the number of discrete pixels of three component color images for eliminating transverse dispersion in the process of computing holograms. Holograms computed by the iterative Fourier transverse algorithm (IFTA) were loaded on reflective liquid crystal spatial light modulator (LC-SLM) for optoelectronic reconstruction. The experimental result shows that the method is effective.